The application of European standards of excellence for teachers of physical education in Secondary Schools from the technical Supervisors Point of View in Baghdad - Zeina Ibraheem Albayati (الرياضة المعاصرة)
The research aimed to applicate the European standards of excellence in Secondary Schools from the technical Supervisors Point of View in Baghdad. The researcher used the descriptive method on (143) supervisor. The researcher designed a special scale for the Iraqi ministry of education with three fields; social services, students’ satisfaction and procedural operations. The data was collected and treated using SPSS to conclude that social services field require from physical educators to collect information to cope with institutional reality inside school. Students’ satisfaction field shows that physical educators should pay more attention to individual differences among students. Procedural operations field showed that educators should create an environment rich with love, cooperation. Finally the researcher recommended paying attention to students and involving them in problem solving and decision making to create a loving environment inside class.